Corporate Agricultural Investment in First Nation Reserves in Canada: The Case of One Earth Farms - Natcher, David C.; Allen, Tom (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2017)
In 2009, One Earth Farms (OEF) established farming operations on First Nation reserves in Saskatchewan and Alberta, Canada. The partnership that was created with First Nations was seen by some as a new model for Canadian agriculture; one that reduced agribusiness risk while enhancing the economic and social welfare of First Nation communities. Notwithstanding the purported social and economic advantages, by 2014, OEF discontinued its contracts with its First Nation partners. The failings of OEF have since been attributed to a flawed foundation, built on a culture and people with a sense of entitlement. Yet this research has found that conflicting timelines, the misalignment of goals, and failure to deliver on what was most important to First Nations are most attributable to the failing of OEF. In this paper we present important lessons learned that if considered can result in more informed and sustained partnerships between First Nations and the private agricultural sector.